Do Debt-Service Savings and Grants Boost Social Expenditures? - Thomas, Alun (IMF Working Papers; Working Paper ;, 2006)
This paper evaluates whether debt relief and grants can boost social expenditures in lowincome countries. It finds that declines in debt-service help raise social expenditures, but no relationship between grants and social expenditures. Moreover, since the mid-1980s, lowincome countries have managed to fully insulate social expenditures from the effects of budgetary tightening. The magnitude of the impact of these effects on social expenditures, however, is dwarfed by the resources needed to enable these countries to reach the Millennium Development Goals.